KESESUAIAN PEMANFAATAN PERMUKIMAN KECAMATAN DUKUN KABUPATEN MAGELANG TERHADAP POLA RUANG WILAYAH KAWASAN GUNUNG MERAPI DAN SEKITARNYA - , FIRMA RIZKI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are a lot of librarian describing about the development of settlement that does not appropiate with the layout and the utilization of the settlement in village that less of supporting infrastucture and it can be seen in the trouble disaster area. There are a lot of the area that can be the supporting wether the hereditary of local society choses to live in trouble disaster area from the history, culture and economy. The Dukun Sub-district is the one of the places the constitute of the Magelang regency that located in slope of southwest from the Merapi Mountain. The Subdistrict of Dukun is the most closet place from the Merapi Mountain, it is about 4 to 10 kilometers from the top of Merapi Mountain. Reviewed from the impact or eruption of Merapi Mountain on 2010, The Centre of The Vulcanology and Mitigation the Disaster Geology, Merapi Mountain got into the phase of eruption since Tuesday evening, 26th October 2010 and the range of the trouble disaster area reasced 20 kilometers from the top of the Merapi Mountain. Then,it needs from evaluations from the development ot the settlement area in the trouble disaster area so as the negative effect to local society there. Through thir research, analyzed besad on the specific of the settlement utilization in the Sub-district Dukun, Magelang Regency to the development of shape from the area that has been considered the mitigation and reduction the risk of the trouble disaster area from the Merapi Mountain. The research uses of the rationalistic paradigma and deductive kualitative method that has implemented found some discrepancies land in the trouble disaster area (KRB III) Dukun, Sub-district that is about 62,2% whereas, the suitability that land is only about 37,8%. This research then will be validated to the result of the field observation.